2005
DOI: 10.1021/jf0517039
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Traditional and Novel Forages

Abstract: Managing the fatty acid composition of grazing ruminant diets could lead to meat and milk products that have higher conjugated linoleic acid (CLA) concentrations, but forage fatty acid dynamics must be more fully understood for a range of forages before grazing systems can be specified. The fatty acid profiles of 13 different forages, including grasses, legumes, and forbs, grown under greenhouse conditions, were determined. Three separate harvests, at 3-week intervals, were made of each plant material. alpha-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
103
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 19 publications
27
103
3
3
Order By: Relevance
“…Lee et al (2003Lee et al ( , 2009, where red clover silage in British studies contained less alpha linolenic acid as a percentage of total fatty acids. Fatty acid composition of tall fescue silage in the present study (Table 8) is similar to that in past studies evaluating fresh cut tall fescue (Clapham et al 2005) or tall fescue pasture (Noviandi et al 2012b). Red cloverÁtimothy silage in the present study contained more (P 50.001) palmitic (C16:0) and linoleic (C18:2) and less (P B0.001) linolenic acid (C18:3n3) than tall fescue silage (Table 8).…”
Section: Tenderness and Cooking Lossessupporting
confidence: 85%
“…Lee et al (2003Lee et al ( , 2009, where red clover silage in British studies contained less alpha linolenic acid as a percentage of total fatty acids. Fatty acid composition of tall fescue silage in the present study (Table 8) is similar to that in past studies evaluating fresh cut tall fescue (Clapham et al 2005) or tall fescue pasture (Noviandi et al 2012b). Red cloverÁtimothy silage in the present study contained more (P 50.001) palmitic (C16:0) and linoleic (C18:2) and less (P B0.001) linolenic acid (C18:3n3) than tall fescue silage (Table 8).…”
Section: Tenderness and Cooking Lossessupporting
confidence: 85%
“…In general, differences in the fatty acid ratios in meat are most apparent in studies comparing contrasting forage-based diets against concentrate-based diets (Warren et al, 2008b) and could be one explanation as to why there was no differences in the current study, particularly as the n-6:n-3 ratio was as low as 1.05 for the control, with below 3 being typical for beef (Scollan et al, 2006). That stated, fatty acid profiles have been shown to differ among forages, with chicory reported as having higher concentrations of C18 : 3 when compared with grasses (including ryegrass), plantain, turnips, rape, triticale and borage (Clapham et al, 2005). In contrast to the current study, other research found that grazing beef steers on chicory increased the ratio of n-6 to n-3 fatty acids in the meat when compared with steers grazing bermudagrass, cowpea or lucerne but not those grazing pearl millet (Schmidt et al, 2013).…”
mentioning
confidence: 54%
“…In relation to the healthiness of meat, the industry is largely concerned with the total amount of fat and its fatty acid composition, aiming to produce meat with a higher ratio of polyunsaturated fatty acids (PUFA) to saturated fatty acids and the optimal ratio of n-6 and n-3 PUFA (Wood et al, 2004). Fatty acid profiles have been shown to differ among forages, with chicory reported as having a different profile and a higher total concentration of PUFA (C18 : 3n-3) than other forages including ryegrass (Clapham et al, 2005). In the experiment by Schmidt et al (2013), chicory increased the ratio of n-6/n-3 PUFA in the meat of grazing steers when compared with steers grazing bermudagrass, cowpea or lucerne, suggesting that including chicory in the diet of grazing ruminants would alter the total fatty acid concentration and composition of their meat.…”
Section: Introductionmentioning
confidence: 99%
“…Forages thus represent one of the main sources of C18:3n-3 in ruminant diets (Dewhurst et al, 2003;Clapham et al, 2005). In our study, replacing maize silage with legume-cereal mixture and lucerne silages considerably increased the dietary intake of C18:3n-3.…”
Section: Discussionmentioning
confidence: 46%